PENINGKATAN KETERAMPILAN MOTORIK HALUS MELALUI KEGIATAN MENEMPEL BIJI-BIJIAN PADA ANAK DIDIK KELOMPOK B DI TK BUKIT PERMAI 2 DESA KAMPILI KABUPATEN GOWA - Silvia; Nur Alim Amri; Tasrif Akib (STKIP Subang, 2022)
This study aims to determine Improving Fine Motor Skills Through Grain Sticking Activities in Group B Children in Bukit Permai 2 Kindergarten, Kampili Village, Gowa Regency. This type of research is class action research which consists of planning, implementation, observation, and reflection. The subjects in this study were group B children with a total of 15 children consisting of 9 boys and 6 girls. Data collection techniques used were observation and documentation. The instruments used are observation and documentation sheets. The data analysis used is descriptive qualitative. The results showed that in the first cycle of 15 children, in improving fine motor skills through the activity of sticking grains, the average value was 34.67% with the criteria for starting to develop (MB), while in the second cycle, where the 15 children obtained an average -an average of 81.17% with very well developed criteria (BSB). Based on the results of the above study, it can be concluded that improving fine motor skills through sticking seeds in group B children at Bukit Mai 2 Kindergarten, Kampili Village, Gowa Regency has increased.